Venous tromboembolism problems and nursing care in perinatal period [Perinatal dönem venöz tromboemboli sorunlari ve hemşirelik bakimi] - (:unkn) unknown (My University, 2004)
Venous tromboembolism in perinatal period is a major health problem relating to maternal mortality in developed and developing countries. Our purpose in this article is to define predisposing factors for venous tromboembolism which is an important health problem in primary health care system context in order to help early recognition of signs and symptoms, to decrease maternal morbidity and mortality rates, and to improve and enhance level of perinatal health care.